Patient-Controlled Analgesia (PCA): Intravenous Administration (IV-PCA) versus Oral Administration (Oral-PCA) by Using a Novel Device (PCoA® Acute) for Hospitalized Patients with Acute Postoperative Pain—A Comparative Retrospective Study. (4th May 2021) - Wirz, Stefan; Seidensticker, Stefanie; Shtrichman, Ronit
Abstract : Background . Acute postoperative pain delays recovery and increases morbidity and mortality. Opioid therapy is effective but is accompanied by adverse reactions. Patient-controlled analgesia (PCA) enables self-administration of analgesics. Oral-PCA is a safe and beneficial alternative to intravenous (IV) PCA. We have developed a novel Oral-PCA device, which enables self-administration of solid pills to the patient's mouth. This is a retrospective study comparing the effectiveness and usability of this novel Oral-PCA with those of IV-PCA. Methods . Medical records of patients who received PCA following gynecology and orthopedic surgeries were analyzed. The control cohort ( n = 61) received oxycodone by IV-PCA. The test cohort ( n = 44) received oxycodone by Oral-PCA via the PCoA Acute device. Outcome measures include the Numeric Rating Scale (NRS) score at rest and movement, side effects, technical difficulties, bolus dose administered, and bolus dose requested. Results . Patient demographics, initial NRS, and PCA duration were comparable between cohorts. NRS reduction in rest and movement was stronger in the Oral-PCA cohort (rest: 1.61 and 2.27, P = 0.077; movement: 2.05 and 2.84, P = 0.039), indicating better pain control and mobility for Oral-PCA. Side effect rates were comparable between cohorts (9% and 11% of patients who experienced side effects, P = 1.000). The rate of technological difficulties was higher in the Oral-PCoA cohort (19.7% and 36.4%, P = 0.056). The mean total bolus dose administered to patients was comparable in both cohorts (18.32 mg and 21.14 mg oxycodone, P = 0.270). However, the mean total boluses requested by patients during lockout intervals were lower in the Oral-PCA cohort (12.8 mg and 6.82 mg oxycodone, P = 0.004), indicating better pain control. Conclusions . Oral-PCA by using PCoA® Acute provides pain control and usability which is noninferior to the IV-PCA, as well as superior to pain reduction in rest and movement. These results, along with the noninvasiveness, medication flexibility, and reduced cost, suggest the potential of Oral-PCA, by using PCoA Acute, to replace IV-PCA for postoperative analgesia.